Analysis of Polyphenolic Compounds in Extracts from Leaves of Some Malus domestica Cultivars: Antiradical and Antimicrobial Analysis of These Extracts. (14th December 2016) - Sowa, Alina; Zgórka, Grażyna; Szykuła, Aleksandra; Franiczek, Roman; Żbikowska, Beata; Gamian, Andrzej; Sroka, Zbigniew
Abstract : In this study, methanol, ethyl acetate, water extracts, and precipitate were obtained from leaves of Malus domestica cultivars: Golden delicious, Jonagold, Elstar, Ligol, and Mutsu. Antiradical activity of these extracts was measured using the A B T S + ∙ radical, and antimicrobial activity was measured with the disk-diffusion method. Phenolic compounds were measured with the colorimetric method and identified with high performance liquid chromatography (HPLC). The highest antiradical activity was observed for the Jonagold variety, and in particular strong activity was noted for ethyl acetate extracts. Antimicrobial activity was observed against strains of Staphylococcus aureus, Enterococcus faecalis, and the fungus Candida glabrata . Particularly susceptible to the extracts activity appeared to be Staphylococcus aureus, but the growth of Candida glabrata was inhibited in the presence of ethyl acetate extracts. With the HPLC method we identified a high amount of phloridzin (above 500 mg per g of ethyl acetate extracts), lower amounts of hyperoside, isoquercitrin, and quercitrin, and traces of p -hydroxybenzoic and chlorogenic acids. The contribution of phloridzin to antiradical activity of methanol and ethyl acetate extracts was very high (above 90%). In water extract the contribution of phloridzin was between 38.9 and 55.2%, chlorogenic acid 22.7 and 36.1%, and hyperoside 12.2 and 13.3%.